SCOSS: A global Sustainability Coalition for Open Science Services - Proudman, Vanessa (Septentrio Conference Series, 2017)
Watch the VIDEO here. The transition to a more far-reaching OA and Open Science is often very much dependent on services and on an infrastructure embedded in workflows to deliver on policy. However, the sustainability of Open Access or Open Science services is often a long way from being assured. A relatively new global coalition called SCOSS will enable the international research community, through its institutions and funding organisations, to take responsibility for sustaining those services. It will do this by providing a new co-ordinated cost-sharing framework to ensure that non-commercial OS services that underpin the development of wider global Open Access and Open Science are sustained in the future. The SCOSS group makes recommendations on what to fund and why based on a rigorous evaluation procedure where services are invited to apply and provide extensive information to the SCOSS group. Applicants provide information on the service’s value to communities such as funders, universities, libraries, authors, research managers, repositories, etc.; information on the governance structure, the technical solution, costs, sustainability measures, and their plans for the future. SCOSS is currently in the middle of a pilot to test the concept. Current SCOSS members include the Australasian Open Access Strategy Group (AOASG), the Council of the Australian University Librarians (CAUL), LIBER, EIFL and SPARC Europe with other organisations following the pilot and advising such as the Confederation of Open Access Repositories (COAR), the European Research Council (ERC), the European University Association (EUA), and others. This presentation will outline the Terms of Reference of the coalition, the case, the SCOSS governance structure, experience with the pilot and challenges to date. This session is of interest to those who are interested in helping the user community to sustain an Open Access and Open Science infrastructure to help implement policy goals, and finding out how they can contribute to making that happen.